Kinerja Thermoelectric pada Kotak Pendingin Berdasarkan Rangkaian Thermoelectric dan Putaran Fan Wind Tunnel - Munawir, Munawir; Sasongko, Mega Nur; Hamidi, Nurkholis (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
A thermoelectric cooler (TEC ) is a component of an electric solid-state cooler that works as a heat pump in the cooling process. Utilizing the peltier effect that is when an electric current is flowed heat absorption occurs on both sides of the thermoelectric and the release of heat on the other side. The use of thermoelectric as a coolant in cool box systems has been widely studied. The purpose of this study was to determine the performance of the cooler using thermoelectric based on the circuit and air velocity in the wind tunnel. The studied performance includes temperature difference, heat absorption, and coefficient of performance. The method used in this study is a real experimental method, with research variables namely series and parallel thermoelectric series and wind tunnel air velocity. Data were taken in the form of cool room temperature cold side temperature, hot side temperature, heatsink temperature, and ambient temperature. Thermoelectric connectivity electrically uses series and parallel circuits and is thermally arranged in series. The results showed that the thermoelectric circuit and wind tunnel air velocity affect the performance of the thermoelectric. Thermoelectric with series circuit produces the highest COP absorption compared to the parallel circuit. The highest performance thermoelectric series is obtained at an airspeed of 9.8 m/s. in these conditions the temperature difference (AT) produced reaches 19oC. the heat absorption (qc) reaches 34.26 watts and the COP reaches 0.89